Cellular quota of organic substance and of chlorophyll a isometric dependence - (:unkn) unknown (К.: Фітосоціоцентр, 2013)
Cellular quota of organic substance (mоs, pg/cell) on quota of chlorophyll a (mchla, pg/cell) isometric dependences have been obtained for eleven species of Bacillariophyceae mов=117.8×mchla (r2=0.997) and for six species of Dinophyceae mов=402.5×mchla (r2=0.986). It could explain the high degrees of correlation for two dependencies in optimal conditions of algae cultures growth. The difference in proportionality coefficients indicates physiological features of the chemical composition of Bacillariophyceae and Dinophyceae cells.